IgG4‐related prostatitis: A rare cause of steroid‐responsive obstructive urinary symptoms. (17th October 2012) - Hart, Phil A; Smyrk, Thomas C; Chari, Suresh T
Abstract IgG4‐related disease is an idiopathic, systemic fibroinflammatory disease that can affect a wide variety of sites, including several in the genitourinary system. We describe a patient with steroid‐responsive urinary symptoms and an abnormal digital rectal exam that were secondary to IgG4‐related prostatitis. We discuss the importance of recognizing this condition and differentiating it from prostate cancer, which can present similarly.